CC-486 (oral azacitidine) in patients with myelodysplastic syndromes with pretreatment thrombocytopenia. (September 2018) - Garcia-Manero, Guillermo; Scott, Bart L.; Cogle, Christopher R.; Boyd, Thomas E.; Kambhampati, Suman; Hetzer, Joel; Dong, Qian; Kumar, Keshava; Ukrainskyj, Stacey M.; Beach, CL; Skikne, Barry S.
Highlights: Post-hoc analysis of 14- or 21-days 300 mg CC-486 per 28-day cycle in MDS patients. At study entry: ≤75 × 10 9 /L (Low Platelets) vs >75 × 10 9 /L (High Platelets) cohorts. Overall response rates: 38% in Low Platelets and 46% in High Platelets cohorts. Patients with pretreatment thrombocytopenia: 5 attained CR; 9 attained platelet HI. CC-486 was well-tolerated; no increase in bleeding events across Platelet cohorts. Abstract: Thrombocytopenia is among the strongest predictors of decreased survival for patients with myelodysplastic syndromes (MDS) across all prognostic risk groups. The safety and efficacy of CC-486 (oral azacitidine) was investigated in early-phase studies; we assessed clinical outcomes among subgroups of MDS patients from these studies, defined by presence or lack of pretreatment thrombocytopenia (≤75 × 10 9 /L platelet count). Patients received CC-486 300 mg once-daily for 14 or 21 days of repeated 28-day cycles. Overall, 81 patients with MDS, median age 72 years, comprised the Low Platelets (n = 45) and High Platelets (n = 36) cohorts. Pretreatment median platelet counts were 34 × 10 9 /L and 198 × 10 9 /L, respectively. Grade 3–4 bleeding events occurred in 2 patients in the Low Platelets and 1 patient in the High Platelets groups; events resolved without sequelae. Treatment-related mortality was reported for 7 patients, 5 of whom had pretreatment platelet values <25 × 10 9 /L. Overall response rates were 38% and 46% in the Low Platelets and High Platelets groups, respectively. Five thrombocytopenic patients attained complete remission and 9 attained platelet hematologic improvement. In both cohorts, platelet counts dropped during the first CC-486 treatment cycle, then increased thereafter. Extended CC-486 dosing was generally well tolerated and induced hematologic responses in these patients regardless of pretreatment thrombocytopenia.